2017
DOI: 10.1021/acs.cgd.7b00799
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Optical Monitoring of New Pathways in the Metal-Induced Crystallization of Amorphous Ge

Abstract: We use high-resolution optical microscopy to characterize in situ the processes at play during the Al-induced crystallization of amorphous Ge. In addition to the well-established aluminum-induced layer exchange (ALILE) process, we demonstrate the existence of another crystallization mechanism with different kinetics and spatial extension using in situ monitoring. Further, ex situ characterizations show that both processes are active in our samples. The ALILE process is found to create a single Ge layer and 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Surely, the thickness of the a-Ge film and its morphology will influence the aforementioned energies. This interpretation provides a better understanding of the large scatter in MIC temperatures for the same couples registered via various experimental techniques [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Surely, the thickness of the a-Ge film and its morphology will influence the aforementioned energies. This interpretation provides a better understanding of the large scatter in MIC temperatures for the same couples registered via various experimental techniques [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Thermal evaporation is suitable for low melting point materials (such as metals), whereas s electron-beam (e-beam) evaporation is suitable for high melting point materials (such as semiconductors). 50,99–107 Katsuki et al . 99 deposited Al (134 nm)/a-Ge (108 nm) on SiO 2 by vacuum evaporation at the room temperature with a base pressure of 10 4 Pa. Alford et al .…”
Section: Preparation Methodsmentioning
confidence: 99%
“…In this study, p-Ge clusters of up to 2 mm in diameter were found to grow laterally on the lm plane surrounded by Ge-depleted zones of about 100 nm width. Very recently, Pelati et al 106 have also studied the nucleation and growth of Al/a-Ge system by in situ optical microscopy.…”
Section: Metal-induced Crystallization Mechanismmentioning
confidence: 99%
See 1 more Smart Citation